Reactions in the Photocatalytic Conversion of Tertiary Alcohols on Rutile TiO2(110). Issue 40 (28th August 2019) - Courtois, Carla; Eder, Moritz; Schnabl, Kordula; Walenta, Constantin A.; Tschurl, Martin; Heiz, Ulrich
Abstract: According to textbooks, tertiary alcohols are inert towards oxidation. The photocatalysis of tertiary alcohols under highly defined vacuum conditions on a titania single crystal reveals unexpected and new reactions, which can be described as disproportionation into an alkane and the respective ketone. In contrast to primary and secondary alcohols, in tertiary alcohols the absence of an α‐H leads to a C−C‐bond cleavage instead of the common abstraction of hydrogen. Surprisingly, bonds to methyl groups are not cleaved when the alcohol exhibits longer alkyl chains in the α‐position to the hydroxyl group. The presence of platinum loadings not only increases the reaction rate but also opens up a new reaction channel: the formation of molecular hydrogen and a long‐chain alkane resulting from recombination of two alkyl moieties. This work demonstrates that new synthetic routes may become possible by introducing photocatalytic reaction steps in which the co‐catalysts may also play a decisive role. Abstract : Breaking ground : The photoreforming of tertiary alcohols on TiO2 (110) follows an unexpected reaction channel, selective disproportionation to an alkane and the respective ketone. When the catalyst is decorated with Pt clusters, the overall reaction rate increases. In addition to ketone formation, a new reaction pathway is observed, hydrogen evolution and alkane dimerization.